Judicialização do direito à saúde: descrição e análise de conflitos exemplares na cidade de Mossoró/RN - Medeiros, Thomas Blackstone de (Universidade Federal Rural do Semi-Árido, 2021)
The present work aims to analyze the phenomenon of the judicialization of health in the Municipality of Mossoró/RN, especially from the examination of judicial processes that involve the provision of material health benefits to local users of the Unified Health System. worked to discuss the foundation and theoretical construction of the right to health, as well as the main doctrinal and jurisprudential arguments, favorable and unfavorable, in relation to the realization of the right to health through the judicial system. Then, data were collected, in the Federal and State Courts, of the lawsuits seeking the granting of supplies, medicines and surgical procedures of interest to health, which have the defendant in the Municipality of Mossoró/RN, as well as interviews with the subjects involved in the judicialization process, also discussing the impacts and consequences of this practice. Finally, there was a need to define criteria and parameters in judicial decisions involving the right to health, as well as the strengthening of public policies involving the realization of this right, based on the integrated performance of entities and civil society itself, in order to prevent the Judiciary from being used as the main route to access health services, which ends up generating several conflicts and inequities in the system itself
Keywords: Conflitos; Direito à saúde; Judicialização; Poder judiciário; Conflicts; Right to health; Judicialization; Judicial branch; CIENCIAS SOCIAIS APLICADAS::DIREITO